Indian Council of Medical Research (ICMR)-Sickle cell disease (SCD) Stigma Scale for India (ISSSI): development and psychometricsResearch in context - Bontha V. Babu; Yogita Sharma; Parikipandla Sridevi; Deepa Bhat; Shaily B. Surti; Jatin Sarmah; Madhusmita Bal; Manoranjan Ranjit; Rabindra K. Jena (The Lancet Regional Health - Southeast Asia)
Summary: Background: Sickle Cell Disease (SCD) places a significant psychological and social burden on patients and their caregivers, often leading to stigma that further diminishes their quality of life. Despite the huge burden of SCD and associated stigma in India, not much research has been done, and no stigma measurement tool is available. Hence, the Indian Council of Medical Research (ICMR) has undertaken a multi-centric study to develop the ICMR-SCD Stigma Scale for India (ISSSI). Methods: A systematic approach was employed, beginning with item generation, content validity assessment, pretesting and psychometric validation. This process included exploratory factor analysis demonstrating strong factor loadings. Subsequently, confirmatory factor analysis was conducted to assess model fit, leading to refined scales of 16 items for patients and 17 items for caregivers. Findings: This study explicitly developed and validated the ISSSI for Indian SCD patients (ISSSI-Pt) and their caregivers (ISSSI-Cg). The finalized scales capture multidimensional aspects of stigma, including familial and reproductive, social disclosure, illness burden, interpersonal, and healthcare interaction challenges. The findings underscore the scales’ psychometric robustness and utility in clinical and research settings. Interpretation: The methodological rigour employed in the scale development makes it a robust tool for understanding SCD-related stigma among Indian SCD patients and their caregivers in clinical and research contexts. The development of the ISSSI represents a significant advancement in understanding and addressing the multifaceted stigma associated with SCD in India. Future studies should apply these scales across diverse cultural and linguistic contexts to enhance their generalizability and impact. Funding: Indian Council of Medical Research (Grant Number: NTF/SCD-Stigma/2022/SBHSR).